'The desire for a harmonious interaction': A qualitative study of how healthcare professionals in community‐based dementia teams perceive their role in reaching and supporting family caregivers from minority ethnic backgrounds. Issue 13 (15th October 2020) - Gulestø, Ragnhild; Halvorsrud, Liv; Bjørge, Heidi; Lillekroken, Daniela
Abstract: Aims and objectives: To explore how healthcare professionals in community‐based dementia teams perceive their role in reaching and supporting family caregivers from minority ethnic backgrounds when caring for a family member suffering from dementia or cognitive impairment. Background: Despite increased focus on barriers to accessing the dementia healthcare service for family caregivers from minority ethnic backgrounds, the lack of knowledge on how to address these barriers in order to reach and support this group is evident. Design: The study has a qualitative, explorative design. The principles of consolidated criteria for reporting qualitative research (COREQ) were applied for reporting methods and findings. Methods: Based on data from semi‐structured interviews ( n = 9) conducted in two large Norwegian municipalities, a thematic analysis influenced by Braun and Clarke was used. The analytical findings draw on Pierre Bourdieu's theoretical concepts of field, habitus and capital . Findings: 'The desire for a harmonious interaction' was identified as an overarching theme. However, while desirable, the analysis shows that healthcare professionals in community‐based dementia teams do not always succeed in reaching and supporting family caregivers from minority ethnic backgrounds. The study reveals that the dementia healthcare service is a complex, normative and sometimes rigid system that requires a number of distinct attributes to navigate. Conclusions: The different social structures within the dementia healthcare service can both create and retain barriers that prevent family caregivers from minority ethnic backgrounds from receiving support on their own terms. Relevance to clinical practice: A practical implication of allowing critical reflection on the dementia healthcare service is that it provides opportunities for discussion. Healthcare professionals in community‐based dementia teams need to reflect on how normative ideals and 'taken‐for‐granted' mindsets can affect their ability to reach and support family caregivers from minority ethnic backgrounds.